HADIS BERPIKIR KRITIS SEBAGAI BASIS PENGUATAN KEMAMPUAN BERPIKIR KRITIS DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA KARTIKA 1-2 - Dimas Tri Is Koerniansyah; Mhd Ary Hamzah; Muhammad Roihan Nasution (SHAHIH (Jurnal Ilmu Kewahyuan), 2026)
This study examines seemingly contradictory hadiths about the Prophet Muhammad‘s practice of qunut in Fajr and Maghrib prayers. Using the method of ta‟wil mukhtalif al-hadith, this article aims to contextualize, analyze, and reconcile these narrations. The qualitative text-based approach reveals that the variations in qunut practice are not actual contradictions but situational diversities, reflecting flexibility in prophetic guidance. This research highlights the significance of ta‟wil mukhtalif in responding to accusations of hadith inconsistency.